Digital Transformation, Big Data and Research Landscape in Digital Communication - Imam Syafganti (Ikatan Sarjana Komunikasi Indonesia, 2018)
The digitization of communications technology has led to an intense interaction between human and digital-based technology. A large number of digital data traces produced by humans as a result of that activity. Such data is commonly referred to Big Data. The availability of Big Data as a digital data source in turn, opens opportunities for communication scientists to be able to use that data to get the patterns and trends of human activities that have been done through social research. It is necessary to understand the basic concept of the Big Data, using appropriate tools and adequate access to the data, and appropriate research method in order to be able to conduct research by using such digital data. This paper aims to describe the potential of Big Data for the purposes of communication research, the use of appropriate tools, techniques and methods and to identify potential research directions in the digital realm. Some limitations and critical issues related to the research validity, population and sample, as well as ethics in digital media research method were also discussed.